Model Predictive Control for Force Control in Milling. Issue 1 (July 2017) - Stemmler, S.; Abel, D.; Schwenzer, M.; Adams, O.; Klocke, F.
Abstract: Milling is one of the most flexible and productive manufacturing processes for machining metals. In the case of rough milling as much material as possible should be removed in as little time as possible. Therefore, a high cutting force is desirable. The maximum force is thus a suitable control variable to reduce the manufacturing time. The cutting force is related to the feed velocity. The relationship can be described by force models. They in turn can be used to determine the maximum feed velocity for a given force. This maximum feed velocity can be used as a reference, which shall not be exceeded. Hence, a Model-based Predictive Controller (MPC) manipulates the desired feed velocity of the machine with respect to the machine behavior. This MPC shows good performance in the case of feed velocity references in time-domain. Though, the feed velocity reference depends on the position of the cutting tool through the workpiece. Hence, an approach shall be described which enables force control in position-domain. Therefore, the existing MPC is extended to a 2-Layer-MPC. An additional MPC works as a reference generator transforming the reference in position-domain into time-domain. Furthermore, an approach is described which allows position dependent feed velocity control without an additional MPC. Finally, the presented approaches are implemented and validated on a real machining center.